Acetyl shikonin induces IL-12, nitric oxide and ROS to kill intracellular parasite Leishmania donovani in infected hosts. Issue 66 (28th June 2016) - Charan Raja, Mamilla R.; Srinivasan, Sujatha; Subramaniam, Shankar; Rajendran, Narendran; Sivasubramanian, Aravind; Kar Mahapatra, Santanu
Abstract : Acetyl shikonin (AS), a naphthoquinone isolated from Arnebia nobilis, was tested against visceral leishmaniasis in this study, revealing that AS provides a chemo-immunotherapeutic strategy against visceral leishmaniasis. Abstract : Acetyl shikonin (AS), a naphthoquinone isolated from Arnebia nobilis, was tested against visceral leishmaniasis (VL) in this study. AS induced anti-VL activity was examined for a number of intracellular amastigotes in Giemsa-stained BALB/C derived macrophages in vitro and hepatic-splenic parasite burden by the stamp smear method in vivo . Mediators of AS induced anti-VL were studied by analysis of nitrites and reactive oxygen species (ROS) and were further confirmed using their inhibitors. The effect of AS on interleukin (IL)-12 and IL-10 was analyzed by ELISA and RT-PCR for infected macrophages. AS treatment caused a nitrite and ROS mediated decrease in the parasite load in murine infected macrophages. These events are associated with the up-regulation of IL-12 and down-regulation of IL-10. In addition, AS was efficient for decreasing the hepatic and splenic parasite load and modulated the IL-12 and IL-10 ratio in splenocytes. In summary, this study revealed that AS provides a chemo-immunotherapeutic strategy against visceral leishmaniasis.